Semi \(c(s)\)-Generalized Closed Sets in Topological Spaces - Nithyakala, R.; Pushpalatha, A. (Journal of Informatics and Mathematical Sciences, 2017)
In this paper, we have introduced a new class of closed set, as a weaker form of closed set namely semi \(c(s)\)-generalized closed set in topological space.